The judgement of Paris in ancient Greek art and literature - Zourgou, Anna (2018)
The Judgement of Paris has been one of the most influential and popular myths throughout antiquity. Significant work has been done by previous scholars on the collection and analysis of artistic representations of the Judgement. This thesis is also looking into the Judgement of Paris in ancient Greek art, but it mainly focuses on the collection and analysis of the references to the myth in Greek literature from the eighth century B.C. to the second century A.D. Special attention is paid to recurring themes and ideological implications that the Judgement story raises, as well as to the interaction between those themes and specific genres. The detailed account and analysis of the references available sheds light not only on the perception of the myth itself, but also on conceptions of morality, beauty, gods, free choice, responsibility and even humour in antiquity. Through this thesis it is possible to see the transformations of the Judgement of Paris throughout centuries of literature, from its very first appearance in Homer’s Iliad to the enjoyable world of Lucian, realising the vast possibilities of this mythological tradition.